What drives the market share changes? Price versus non-price factors - Konstantins Benkovskis; Julia Wörz (Bank of Finland, Institute for Economies in Transition (BOFIT), 2013)
The paper proposes a theoretical framework to explain gains and losses in export market shares by their price and non-price determinants. Starting from a demand-side model à la Armington (1969), we relax several restrictive assumptions to evaluate the contribution of unobservable changes in taste and quality, taking into account differences in elasticities of substitution across product markets. Using highly disaggregated trade data from UN Com-trade, our empirical analysis for the major world exporters (G7 and BRIC countries) reveals the dominant role of non-price factors in explaining the competitive gains of BRIC countries and concurrent decline in the G7's share of world exports.
URN:NBN:fi:bof-201408072226
Keywords: C43; F12; F14; L15; 330; export market share decomposition; non-price competitiveness; real effective exchange rate